The Digital Da’wah Movement: A Phenomenological Question of Urban Sufism Women - Jamalul Muttaqin (Lembaga Kajian dan Pengembangan Sumberdaya Manusia, 2021)
Today's socio-religious movement cannot be separated from the explosion of the era of modernism which demands a more dynamic, flexible and not rigid propaganda movement in dealing with the problems of people's lives. This phenomenon is marked by the rise of digital da'wah that comes into people's lives, particularly in Indonesia. The urban Sufism movement once emerged in response to this phenomenon, but what about women's urban Sufism? Where is their position today? This research uses a qualitative approach. Sources of data obtained from several books, journals, articles and other scientific works. More deeply, this paper will discuss the bibliography from time to time, from conventional forms of Sufism to urban Sufism. Either through religious tariqa, majlis dhikir, or certain religious institutions that today continue to flourish in Indonesia through digital media. Sufi groups are